The effect of functionalized single walled carbon nanotube with octadecylamine on efficiency of poly-(3-hexylthiophene): [(6,6)] phenyl C61 butyric acid methyl ester organic solar cells - Cakmak, Gulbeden; Guney, H. Yuksel; Yuksel, Sureyya Aydin; Gunes, Serap (ELSEVIER, 2015)
We fabricated bulk heterujunction (BM) solar cells with a configuration lTO/PEDOT:PSS/P3HT:PCBM:o-SWNT/A1 that consisted of different carbon nanotubes concentrations functionalized with octadecylamine (o-SWNT). The three solar cells which consisted of o-SWNT concentrations of 0.01%, 0.001% and 0.0001% by weight were prepared at the same process conditions. The absorption measurements of active layer (P3HT:PCBM: x wt% of o-SWNT) and current-voltage measurements of solar cells have shown that V-oc does not change depending on the used contribution rates. However, J(sc) has increased by 23.8% in solar cells that are fabricated with o-SWNT concentrations of 0.001 wt% compared with solar cell without o-SWNT. The power conversion efficiency has also increased by 31.8%. While IPCE is about 37% in 350 nm in the reference solar cell, IPCE of the solar cell comprised of o-SWNT of 0.001 wt% is about 45%. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Organic solar cell; Functionalized carbon nanaotabes; Octarlecylamine; P3HT:PCBM; CONJUGATED POLYMERS; PERFORMANCE; P3HT/PCBM; COMPOSITES; SOLVENT; TRANSPORT; Physics